Ricardo Palma’s critical review on the graphic aspect of his Peruvian Traditions (Tradiciones peruanas) (1872-1897) - Mondragón Miranda, Mariela (2020)
Ricardo Palma’s critical review on the graphic aspects of printing in Peru at the end of the 19th century was expressed around the transformations of the Peruvian Traditions. We have analyzed the graphic context regarding printing and the materiality of the first three editions, where we have seen the change of a book of ancient aesthetics in modern context until becoming an artistic and industrial bibliographic piece, which was also worth its author’s review. This also allows us to learn about Ricardo Palma as a writer with a tenacious aesthetic sense.